KNOWLEDGE, PRACTICE OF HAND WASHING AMONG HEALTH STAFF AND SOME RELATED FACTORS IN DEVELOPING COUNTRIES, 2011-2020: A SCOPING REVIEW (Vietnam Journal of Community Medicine, 2022)
Objective of the study was to review knowledge, practice of hand washing among health staff andsome related factors in developing countries during 2011-2020. Sduty design was a scoping review.The number of reviewed articles were 37 including international and Vietnam papers. Results shownthat the knowledge in hand washing among healt staff was rather good (range 54-94.5%). Nurseswas more frequently to have hand washing than that of doctors. Factors such as difficult to accessto hand washing facilities, overload of patients and works, lack of soap and alcol fluid. Contributedto the reduction of hand washing. Other factors such as training, availability and access to hygienefacilities were to increase the rate of hand washing among health staff. To increase hand washingamong health staff, these factors should be considered in health facilities.
Keywords: Knowledge, practice, influencing factors, hand washing, health staff, developing countries, 2011-2020.